2022
DOI: 10.1177/01617346211069882
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate U-Net Model for Fetal Ultrasound Image Segmentation

Abstract: U-Net based algorithms, due to their complex computations, include limitations when they are used in clinical devices. In this paper, we addressed this problem through a novel U-Net based architecture that called fast and accurate U-Net for medical image segmentation task. The proposed fast and accurate U-Net model contains four tuned 2D-convolutional, 2D-transposed convolutional, and batch normalization layers as its main layers. There are four blocks in the encoder-decoder path. The results of our proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Five studies assessed deep learning for automated measurement of the FL only 59–63 and two studies assessed automated measurement of AC only 64,65 . There were four studies assessing correct detection of the fetal abdominal standard plane (FASP) using AI 66–69 and five studies assessed various combinations of two or more fetal biometry measurements 70–74 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies assessed deep learning for automated measurement of the FL only 59–63 and two studies assessed automated measurement of AC only 64,65 . There were four studies assessing correct detection of the fetal abdominal standard plane (FASP) using AI 66–69 and five studies assessed various combinations of two or more fetal biometry measurements 70–74 …”
Section: Resultsmentioning
confidence: 99%
“…Gofer were four studies assessing correct detection of the fetal abdominal standard plane (FASP) using AI [66][67][68][69] and five studies assessed various combinations of two or more fetal biometry measurements. [70][71][72][73][74] Ten studies focused on the use of AI in fetal cardiac imaging (Table 4). retrieves the right and left ventricular outflow tracts from a threedimensional (3D) volume of the fetal chest and found they were correctly identified 91.7% and 94.4% of the time, respectively.…”
Section: Number Of Patients Inclusion Criteria Description Of Artific...mentioning
confidence: 99%
“…Our previous paper proposed Fast-Unet 39 , which used convolution layers with a 5 × 5 kernel and 2 × 2 stride. Leaky Rectified Linear Units (Leaky ReLU) with 0.2 negative slope coefficient are set as the activation function in the encoder path and the ReLU activation function in the decoder path.…”
Section: Methodsmentioning
confidence: 99%
“…We have proposed a modification of Fast-Unet to overcome the problem. Fast-Unet is a high-performance novel CNN architecture that aims to segment fetal ultrasound images 39 . The key point in the network is using 2 × 2 stride in the convolution layers that downsamples the spatial resolution of feature maps, thus making the network needless to the pooling layer.…”
Section: Introductionmentioning
confidence: 99%
“…The U-Net based architecture has also been widely applied in many segmentation tasks, such as liver ( 7 , 8 ), lung ( 9 ), tumor segmentation ( 10 , 11 ), and prostate ( 12 , 13 ). U-Net has also attracted many attentions in the field of ultrasonic images such as segmentation of ovary ( 14 ), fetal head ( 15 ), and breast ( 16 ). As for CHD diagnosis, it has also been reported that AI-based automatic auscultation may improve the accuracy of CHD screening ( 17 ).…”
Section: Introductionmentioning
confidence: 99%